Peningkatan Kemampuan Membaca Permulaan Menggunakan Puzzle Pada Siswa Kelas I SD - Raudhatul Jannah Assubaidi; Rudi Ritonga (Mitra Pilar: Jurnal Pendidikan, Inovasi, dan Terapan Teknologi, 2023)
Abstract This research employs the Classroom Action Research (CAR) method to evaluate the effectiveness of implementing puzzle media in enhancing the early reading skills of first-grade students in an elementary school. The results indicate a significant improvement in students' early reading skills following the implementation of puzzle media. In the first cycle, approximately 63% of students successfully achieved the Minimal Competency Level (MCL), while in the second cycle, the percentage of students reaching MCL increased to around 83%. Puzzle media aids students in understanding the relationship between sounds and letters, while also facilitating interactive and engaging learning. The implementation of puzzle media proves to be effective in enhancing the early reading abilities of first-grade students. Abstrak Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) untuk mengevaluasi efektivitas penerapan media puzzle dalam meningkatkan kemampuan membaca permulaan siswa kelas I di sebuah sekolah dasar. Hasil penelitian menunjukkan adanya peningkatan yang signifikan dalam keterampilan membaca permulaan siswa setelah penerapan media puzzle. Pada siklus I, sekitar 63% siswa berhasil mencapai KKM (Kompetensi Minimal Minimal), sedangkan pada siklus II, persentase siswa yang mencapai KKM meningkat menjadi sekitar 83%. Media puzzle membantu siswa memahami hubungan antara bunyi dan huruf, serta memfasilitasi pembelajaran yang interaktif dan menarik. Penerapan media puzzle efektif dalam meningkatkan kemampuan membaca permulaan siswa kelas I.